Influence of fertigation on fruit yield, water use and distribution efficiency and economics of guava (Psidium guajava L.). - PRAMANIK, SANJIT; PATRA, S. K. (Journal of Soil and Water Conservation, 2021)
A field experiment was conducted during 2009-2010 and 2010-2011on a sandy loam soil to assess the fertigation levels on fruit yield, water use and water distribution efficiency and economics of guava (Psidium guajava L.). The treatments consisted of four irrigation levels (i.e. 1.0 IW/CPE, and 0.60, 0.80 and 1.00ETC) and three nitrogen fertigation levels (0.80, 1.00 and 1.20 of recommended dose of N) was laid out in a split plot design (SPD) with three replications. The results showed that fruit yield increased significantly with increase in application of irrigation water and nitrogen fertilizer. However, maximum fruit yield, higher water use efficiency, net return and B: C ratio was registered from drip irrigation at 1.00ETC. Full recommended dose of nitrogen fertilizer was found to be optimal for maximum fruit yield. The water distribution efficiency in drip irrigation system was uniform and higher near the dripper and then decreased consistently with increase in distance both horizontally and vertically. Thus drip irrigation at 1.00ETC with recommended dose of N-fertigation could be recommended for higher fruit yield and economics of guava in the lower Gangetic plain of West Bengal, India. Alternatively, surface irrigation scheduling at 1.0IW/CPE could be advocated if the initial investment for laying the drip irrigation system is an impediment for the guava growers in this region.